Oblicz:
a) 3 razy(-2)+(-3) razy(-2)=
b) (-5) razy(-4)+6 razy(-3)=
c) 7 razy(-40)+9 razy(-5)=
d) 5 razy(-3)+(-8) razy(-10)=
e) (-4) razy(-5)+(-2)razy(-9)+3razy5=
f) 4razy12+(-5)razy(-9)=
g) 20razy(-4)+3razy(-8)=
h) (-2)+3razy(+3)+12razy(-5)+(-1)razy(-20)=

3

Odpowiedzi

2009-11-24T19:54:12+01:00
A) 3 razy(-2)+(-3) razy(-2)= -6+6=0
b) (-5) razy(-4)+6 razy(-3)=20-16=2
c) 7 razy(-40)+9 razy(-5)=-280-45=-325
d) 5 razy(-3)+(-8) razy(-10)=-15+80=65
e) (-4) razy(-5)+(-2)razy(-9)+3razy5=20+18+15=53
f) 4razy12+(-5)razy(-9)=48+45=93
g) 20razy(-4)+3razy(-8)=-80-24=56
h) (-2)+3razy(+3)+12razy(-5)+(-1)razy(-20)=(-2)+9-60+5=48
2009-11-24T19:55:56+01:00
A) -6+6=0
b)20+(-18)=2
c)-280+(-45)=-325
d)-15+80=65
e)20+18+15=53
f)48+45=93
g) -80+(-24)= - 104
h)-2+9+(-60)+20=-33
2009-11-24T20:04:02+01:00
A) 0
b) 2
c) -325
d) 65
e) 53
f) 93
g) -104
h) -33